Agriculture is integrated into the Paris agreement - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
The significant role of agriculture in climate change has been underrepresented in previous years’ discussions and agreements under the United Nations Framework Convention on Climate Change (UNFCCC). CCAFS and partners in the global agriculture community have strived to address this imbalance through several years of engagement with parties and UNFCCC processes. As a result of these efforts, issues directly related to agriculture, such as food production and security are explicitly mentioned in the Paris Agreement concluded by the UNFCCC at its 21st Conference of Parties (COP21) in 2015. The preamble makes specific reference to safeguarding food security and ending hunger, and one Article details the importance of protecting food production when reducing greenhouse gas emissions. In addition, 80% of the Intended Nationally Determined Contributions (INDCs) submitted by countries committed to action on agricultural mitigation, and 90% of INDCs that include adaptation selected agriculture as a priority sector for action, thus creating a framework for climate action in the sector. Human rights, gender, ecosystems and biodiversity, all issues central to agriculture, are also featured within the Paris Agreement. To ensure that a new climate change deal would not close the door on agriculture, CCAFS scientists provided several inputs to the climate change negotiations. These included:  Provision of evidence on agriculture and food security under 1.5C and 2C futures to negotiators through the UNFCCC Structured Expert Dialogue  Production of a guide to UNFCCC Negotiations on Agriculture, which was widely disseminated amongst parties and observers  Formal submissions to the UNFCCC Subsidiary Body for Scientific and Technological Advice (SBSTA) call on Agriculture in 2015  Development and dissemination of policy briefs at key UNFCCC events, including SBSTA and COP21  Provision of technical support to parties in the development of their INDCs and SBSTA submissions  Strategic presence at the COP and SBSTA, including side events with a range of partners to give prominence to developing country perspectives